Non-fasting Changes in Blood Lipids After Three Daily Meals Within a Day in Chinese Inpatients With Cardiovascular Diseases - Tan, Yangrong; Lin, Qiuzhen; Xu, Jin; Zhu, Liyuan; Guo, Liling; Xie, Yingying; Du, Xiao; Zhang, Shilan; Wen, Tie; Liu, Ling (Frontiers in Cardiovascular Medicine, 2022)
Background Non-fasting (i.e., postprandial) lipid detection is recommended in clinical practice. However, the change in blood lipids in Chinese patients with cardiovascular diseases after three daily meals has never been reported yet. Methods Serum levels of blood lipids were measured or calculated in 77 inpatients (48 men and 29 women) at high or very high risk of atherosclerotic cardiovascular disease (ASCVD) in the fasting state and at 4 h after three meals within a day according to their diet habits. Results Female patients showed significantly higher level of high-density lipoprotein cholesterol (HDL-C) than male patients, and the gender difference in other lipid parameters did not reach statistical significance at any time-point. Levels of triglyceride (TG) and remnant cholesterol (RC) increased, while that of low-density lipoprotein cholesterol (LDL-C) decreased significantly after three meals (p < 0.05). Levels of HDL-C, total cholesterol (TC), and non-high-density lipoprotein cholesterol (non-HDL-C) showed smaller changes after three meals. Percent reductions in the non-fasting LDL-C levels after lunch and supper were around 20%, which were greater than that after breakfast. The percent reductions in the non-fasting non-HDL-C levels after three meals were smaller than those in the non-fasting LDL-C levels. Patients with TG level ≥ 2.0 mmol/L (177 mg/dL) after lunch had significantly greater absolute reduction of LDL-C level than those with TG level < 2.0 mmol/L (177 mg/dL) after lunch [–0.69 mmol/L (–27 mg/dL) vs. –0.36 mmol/L (–14 mg/dL), p<0.01]. There was a significant and negative correlation between absolute change in LDL-C level and that in TG level (r = −0.32) or RC level (r = −0.67) after lunch (both p<0.01). Conclusion LDL-C level decreased significantly after three daily meals in Chinese patients at high or very high risk of ASCVD, especially when TG level reached its peak after lunch. Relatively, non-HDL-C level was more stable than LDL-C level postprandially. Therefore, when LDL-C level was measured in the non-fasting state, non-HDL-C level could be evaluated simultaneously to reduce the interference of related factors, such as postprandial hypertriglyceridemia, on detection.